Autism in girls: Invisibility and diagnostic challenges (Research, Society and Development, 2025)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental condition characterized by difficulties in communication, social interaction, and repetitive behaviors. Its prevalence is significantly higher in males, with diagnoses occurring three to four times more frequently than in females. Diagnosis in females often occurs late, frequently in adulthood, due to less evident phenotypic characteristics and compensatory strategies that mask symptoms. Studies show that women with ASD face profound social challenges and, prior to diagnosis, often feel confused and pressured to adapt to social expectations, which may lead to additional difficulties. Objective(s): To analyze the disparities presented in contemporary scientific literature regarding the diagnosis of Autism Spectrum Disorder (ASD) in girls, considering less evident about phenotypic traits and the frequency of delayed diagnosis. Method: This article aims to understand the aforementioned phenomena through a literature review of the last five years on autism and gender, using electronic databases. Conclusion: The manifestations of ASD signs in girls can be easily overlooked due to evaluation criteria standardized for boys. The social camouflaging adopted by girls highlights the need for gender-sensitive diagnostic criteria, ensuring adequate support and reducing the consequences of late diagnosis.